Biosourced Nitrogen‐Doped Microcellular Carbon Monoliths. Issue 2 (21st January 2014) - Brun, Nicolas; Osiceanu, Petre; Titirici, Magdalena M.
Abstract An original approach based on the hydrothermal carbonization of nitrogen‐containing biomass derivatives within the continuous phase of a direct concentrated emulsion is reported for the synthesis of nitrogen‐doped microcellular carbon monoliths. These biosourced foams show promising performances as intrinsic electrocatalysts in the oxygen reduction reaction. Preliminary catalytic properties of powdered versus monolithic samples are discussed and suggest interesting prospects for their introduction within electrochemical devices.